The Value of Islamic Education in The Book of Anggukan Ritmis Kaki Pak Kiai by Emha Ainun Nadjib - Awali Muttaqiin; Unik Hanifah Salsabila; Difa Ul Husna; Yazida Ichsan (Universitas Ahmad Dahlan, 2022)
This study is trying to describe the results of the analysis of Islamic Educational Values in the book of Anggukan Ritmis Kaki Pak Kiai by Emha Ainun Nadjib or commonly called Cak Nun and at the same time looking at the reconstruction of the concept or values of education offered with the needs and challenges of today's education. This study uses a library research approach with direct data sources from the book of Anggukan Ritmis Kaki Pak Kiai and Emha's books relevant to this research based on the analytical methods and content analysis. The results of this study or the Islamic Educational Values that the author found in the book of Anggukan Ritmis Kaki Pak Kiai talk about the peak of one's faith is monotheism, the net is through piety, and its manifestation is Rahmatan Lil 'Alamin. Then, the value of moral education is to question our attitude toward non-Muslims, re-understanding the meaning of Ukhuwah Islamiyah broadly and deeply. What is contained in the value of Islamic Education includes worship as a Manifestation of Love for Allah by understanding the concept of reward more broadly, Prayer, Fasting, Zakat, and Hajj. Meanwhile, the meaning of an educator, according to